On the Correlation between EUV Solar Radiation Proxies and their Long-Term Association - Elias, Ana Georgina (2021)
EUV solar radiation proxies, in particular monthly mean Mg II, Lyman ALPHA flux, F10.7 and Rz, are analyzed during the period 1979-2020. Their variability is compared through a correlation analysis. When the whole period is considered, the linear correlation is greater than 0.95 between each pair of solar proxies if monthly or 12-month running mean series are used. But, when short sub-periods are correlated this value decreases markedly during maximum and minimum solar activity levels. This result may be due to the random noise part of each series as we show it through a "statistical experiment". Their hysteresis along a solar activity cycle is also reproduced as part of this analysis.